(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2020)
NTRODUCTION: Early auditory assessments are important in determining the hearing abilities of children, as well as alterations that may occur at this level. The use ofnon-invasive evaluation methods, which give an approximation of this, allows us to guide the actions to follow in case of deficiency. METHODS:This research is qualitative type, uses Hermeneutic methodology and Spider tool. RESULTS:The results of the process demonstrated that acumetry examinations continue to be valuable in guiding the audiological diagnosis of hearing impairment in its early stages. ANALYSIS AND DISCUSSION:The cost of equipment, the need for health entities and qualified personnel in case of needing sedation of minors for the performance of objective audiological tests merits that these subjective, non-invasive procedures acquire great importance as initial methods of behavioral observation and diagnostic orientation. CONCLUSIONS:Not all acumetry evaluations analyzed meet the criteria of specificity and sensitivity, but they are still effective and of rapid initial diagnostic orientation